Pleasure from pain the schadenfreude tendencies and motivations of Funny Vines audiences - Tope, Dessa Lou Abat 1996- (2017)
"This is an exploratory study that focused on media audience's feeling of schadenfreude or the pleasure from another's misfortune, particularly through the channel, Funny Vines, in Youtube. Specifically, the study wanted to examine the audience's reactions towards videos that could possible elicit schadenfreude and know the motivations behind this emotion that is common despite its negative connotations. A mix ethnographic approach was implemented giving importance to both online and offline audiences in order to gather substantial data to form descriptive layers. The mix of online and offline ethnography complemented the gaps of each methodology in assessing the reactions and reasons for the feeling of schadenfreude of audiences. The study employed a 3-step process of direct observation, self-administered questionnaire, and interview in order to cover the reactions, determine if schadenfreude is present among the audiences, and to know the motivations behind it. The online and offline methods of data collection were similar but differently constructed to fit the units of observation for each. I used thematic analysis in analyzing the data gathered while using the uses and gratification theory as my guide, doing clusters and themes to determine the different motivations, whether they align to present literature or if it's a new one. Throughout the course of this research, I was able to see if schadenfreude is present among audiences of Funny Vines, identify different audiences' sharing habits of the emotion, and discover motivations of audiences with schadenfreude. This study aims to contribute in media audience research particularly in dealing with pleasure and hedonic emotions."